The Role of Pharmacists in Opioid Addiction Management - Dave, Pallav (Indian Journal of Pharmacy & Drug Studies, 2024)
Opioid addiction claims thousands of lives every year in the United States. The prevalence of misuse, abuse, and overdose continues to rise despite the measures and initiatives taken by the federal government and other government agencies to manage the problem. These efforts have led to a re evaluation of the role different healthcare providers can play to ensure the problem is adequately addressed. Being one of the most accessible healthcare providers to patients under opioid therapy, pharmacists are better positioned to deal with opioid addiction. They dispense millions of opioids every year making them better positioned to screen for patients who are likely to develop an addiction problem and refer them to treatment resources before the abuse escalates to opioid use disorder (OUD). The aim of this review is to explore the role of pharmacists in opioid addiction management including prevention, screening, education, naloxone prescribing, counselling, and referral to treatment resources. The review also provides pertinent information regarding the current state of the opioid crisis in the US, including recent data on prevalence and opioid related deaths. Exploring the role of pharmacists is instrumental in coming up with effective measures that can help in opioid addiction management.